Low back pain in the adolescent athlete - De Luigi, A. J. (Physical Medicine & Rehabilitation Clinics of North America, 2014)
Clinicians must have knowledge of the growth and development of the adolescent spine and the subsequent injury patterns and other spinal conditions common in the adolescent athlete. The management and treatment of spinal injuries in adolescent athletes require a coordinated effort between the clinician, patients, parents/guardians, coaches, therapists, and athletic trainers. Treatment should not only help alleviate the current symptoms but also address flexibility and muscle imbalances to prevent future injuries by recognizing and addressing risk factors. Return to sport should be a gradual process once the pain has resolved and the athlete has regained full strength.